ENHANCING MSME MARKETING PERFORMANCE THROUGH KNOWLEDGE MANAGEMENT: DIGITAL CAPABILITY AND DIGITAL INNOVATION AS MEDIATING VARIABLES - Fitri Yutika; Febiwenesya Forever (RADJA PUBLIKA, 2024)
This study examines the impact of Knowledge Management (KM) on Marketing Performance in Micro, Small, and Medium Enterprises (MSMEs), with Digital Capability and Digital Innovation as mediating variables. A quantitative approach was employed, analyzing data from 150 MSMEs in West Kalimantan using Structural Equation Modeling (SEM) with SmartPLS software. The findings reveal that KM significantly influences Marketing Performance both directly and indirectly through Digital Innovation, which acts as a partial mediator. Conversely, Digital Capability does not significantly mediate the relationship between KM and Marketing Performance, indicating its limited role without effective integration into marketing strategies. The results underscore the crucial role of Digital Innovation in enhancing Marketing Performance, suggesting that MSMEs should prioritize innovation-driven strategies supported by robust KM practices. To achieve optimal outcomes, MSMEs are advised to integrate KM with a strong focus on Digital Innovation while improving the application of Digital Capability within their marketing frameworks. These insights provide valuable implications for managerial and policy-level interventions to bolster MSME competitiveness in the digital era.